Meningkatkan Militansi Iman melalui Pengalaman Spiritual: Studi tentang Dampak Camping Rohani bagi OMK di Paroki St. Martinus Bone-Bone - Fernandes Fernando (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study aims to identify and describe the influence of Spiritual Camping on the faith militancy of Catholic Youth (OMK) at St. Martinus Bone-Bone Parish. The activity is designed to strengthen fellowship among OMK members and deepen their spiritual relationship with God. A quantitative descriptive design was employed, involving 120 respondents who participated in the Christmas Camping (December 28-31, 2023) and Luwu Youth Day Camping (July 25-29, 2024) at Bukit Tabor, East Luwu Regency. Data were collected via Google Form questionnaires and analyzed using descriptive statistics. Results indicate that most participants experienced increased spiritual enthusiasm, closeness to Jesus, and active involvement in OMK activities after the camping. Specifically, 31.7% gained new insights, 28.3% were motivated for self-improvement, 12.5% became more prayerful, and 35% increased their engagement in ministry. Additionally, the camping strengthened social bonds and personal-group commitments to church participation. These findings demonstrate that Spiritual Camping effectively enhances OMK’s faith militancy while promoting community cohesion and sustained spiritual commitment.